Preferência de oviposição e ciclo de vida da mosca negra dos citros, Aleurocanthus woglumi ASHBY, 1915 (Hemiptera: Aleyrodidae) em diferentes plantas hospedeiras - Lopes, Gislane da Silva (2010)
The citrus black fly, Aleurocanthus woglumi Ashby, is a pest native to Asia but is widely distributed throughout much of the world and is considered an A2 quarantine pest in Brazil and causing damage in many fruit, especially citrus (orange, lemon and tangerine). Being a pest introduced there is little research related to bio-ecological aspects of A. woglumi environmental conditions of the state of Maranhao, so the study, the oviposition preference, the cycle of life and describe some morphological features of A. woglumi in different hosts. The research was conducted in a greenhouse during the period March 2009 to March 2010, and tests were performed and preferably with no choice in six hosts, while in periods of 48 and 72 hours, in addition to comparative biology mango and orange. Were observed in the tests to A. woglumi shows a preference for ovipositing in Citrus species (lemon, orange and mandarin), maintaining a pattern of non-preference on cashew and guava. There was no statistical difference in duration and viability of the biological cycle of A. woglumi hosts in orange and mango.